THE EFFECT OF USING DUOLINGO APPLICATION AS TEACHING MEDIA TO IMPROVE VOCABULARY MASTERY OF ELEVENTH GRADERS - Reza Artha Mevia; Ahmad Thoyyib Shofi; Lailatul Masruroh (Program Studi Pendidikan Bahasa Inggris, 2024)
This research examines the effectiveness of the Duolingo application in enhancing the vocabulary achievement of eleventh-grade students. Using a quasi-experimental design, the study compares the vocabulary acquisition of students who used the Duolingo app with those who did not. The experimental group received the Duolingo app as treatment, while the control group received conventional instruction without additional intervention. Pre-tests and post-tests were administered to both groups to assess vocabulary skills before and after the treatment. The study was conducted at SMA Nusantara, involving 31 students from eleventh grade A and B. Data collection was taken from multiple-choice tests to measure vocabulary acquisition. Statistical analyses, including independent t-tests, were performed using SPSS 26.0 to compare the vocabulary mastery of both groups. Results indicate that students in the experimental group, who used the Duolingo app, demonstrated significantly higher vocabulary scores compared to the control group. The students who have been taught the Duolingo application get better grades than those who have been taught the traditional method. The findings highlight the efficacy of incorporating technology, such as the Duolingo app, in language learning to improve vocabulary acquisition among students. Further research could explore the long-term effects of using Duolingo and its applicability in diverse educational settings.